Strategi Dinas Tenaga Kerja dalam Perlindungan Pekerja Perempuan (Studi di Kota Cirebon) - irma maulida (Universitas Semarang, 2020)
Work relationship is a relationship between workers and employers that occur after an employment agreement. Although it has created a working relationship between the two parties, in its implementation it is not in accordance with matters that have been agreed or regulated in the legislation in the form of a work agreement. This is interesting to be seen and examined, because if we talk about female workers, actually female workers have privileges or privileges that are not owned by male workers. Although in reality, these rights are not granted or cannot be exercised.The problem in this research is, what are the forms of rights possessed by women workers, and what are the strategies carried out by the Cirebon City Manpower Office in providing protection to female workers.The research method in this writing is descriptive research, with data collection techniques through direct interviews in the Cirebon City Labor Office and Documentation Studies.The results of the study showed that women workers rarely report. This happens because if there is a problem, it can be resolved at the company level. The strategy undertaken by the Manpower Office to provide protection to female workers is to conduct socialization both in class rooms and door to door.Keywords : Work relations; Women Worker; Manpower Office.